2001
DOI: 10.1023/a:1008950713001
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Angiogenesis is essential in wound healing and a common feature in chronic inflammation which is crucially involved in the biological response to biomaterials. A useful system to evaluate the angiogenic activity and the inflammatory potency of various agents is the chorioallantoic membrane (CAM) of the chick embryo. Here we examined its response to different biomaterials. Smooth materials such as PVC or the polyurethane Tecoflex either unmodified or modified by an OH- or N(CH(3))(3)(+)-end group (HEMA or MAPTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…This study was approved by the Animal Ethics Committee, Faculty of Pharmacy, Silpakorn University, Nakhon Pathom, Thailand. In ovo method was performed to investigate the angiogenic activity of asiaticoside using the method described previously [23] with some modifications. Fertilized chicken eggs were incubated in a humidified incubator at 37°C with adjusting slope of the egg tray back and forth for 60°every 2 h.…”
Section: Cytotoxicity Studiesmentioning
confidence: 99%
“…This study was approved by the Animal Ethics Committee, Faculty of Pharmacy, Silpakorn University, Nakhon Pathom, Thailand. In ovo method was performed to investigate the angiogenic activity of asiaticoside using the method described previously [23] with some modifications. Fertilized chicken eggs were incubated in a humidified incubator at 37°C with adjusting slope of the egg tray back and forth for 60°every 2 h.…”
Section: Cytotoxicity Studiesmentioning
confidence: 99%
“…We found that covalent coupling of the peptide using the pAAc strategy resulted in a significant decrease in angiogenesis after seven days, exhibiting the lowest number of novel blood vessels, but strikingly, it increased up to the highest level of angiogenesis of all materials tested in this study in as few as two additional days (Table ). As another readout of the CAM assay, granulation tissue can be determined . Notably, only the covalently coupled peptide also evoked the development of inflammatory granulation tissue (indicated by arrows) after nine days of the assay (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The opening in the shell was sealed with paraffin film (Parafilm, Pechiney Plastic Packaging, Chicago, USA), to prevent dehydration. The eggs were incubated at 37 °C for another 7 or 9 d as described earlier …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, the polyvinyl chloride (PVC) films satisfy some requirements imposed by medical applications, such as chemical inertness, biocompatibility, ease of design and lower cost of the existing technologies [7,8]. An increased concentration of plasticizer significantly reduces the yellowness index of materials after gamma sterilization [9].…”
Section: Introductionmentioning
confidence: 99%